Mannitol Stress Directs Flavonoid Metabolism toward Synthesis of Flavones via Differential Regulation of Two Cytochrome P450 Monooxygenases in Coleus forskohlii - Awasthi, Praveen; Gupta, Ajai Prakash; Bedi, Yashbir S.; Vishwakarma, Ram A.; Gandhi, Sumit G. (Frontiers in Plant Science, 2016)
Cytochrome P450 monooxygenases (CYP450s) are known to play important roles in biosynthesis of all secondary metabolites, including flavonoids. Despite this, few CYP450s have been functionally characterized in model plants and roles of fewer CYP450s are known in non-model, medicinal and aromatic plants. Our study in Coleus forskohlii indicates that flavone synthase (CYP93B) and flavonoid 3’ monooxygenase (CYP706C) are key enzymes positioned at a metabolic junction, to execute the biosynthesis of different sub-classes of flavonoids (flavones, flavonol, anthocynanin, isoflavones etc.) from a common precursor. Such branch points are favored targets for artificially modulating the metabolic flux toward specific metabolites, through genetic manipulation or use of elicitors that differentially impact the expression of branch point genes. Genkwanin, the only flavone reported from C. forskohlii, is known to possess anti-inflammatory activity. It is biosynthesized from the general flavonoid precursor: naringenin. Two differentially expressed cytochrome P450 genes (CfCYP93B, CfCYP706C), exhibiting maximum expression in leaf tissues, were isolated from C. forskohlii. Mannitol treatment resulted in increased expression of CfCYP93B and decrease in expression of CfCYP706C. Metabolite quantification data showed that genkwanin content increased and anthocyanin levels decreased in response to mannitol treatment. Alignment, phylogenetic analysis, modeling and molecular docking analysis of protein sequences suggested that CfCYP93B may be involved in conversion of naringenin to flavones (possibly genkwanin via apigenin), while CfCYP706C may act on common precursors of flavonoid metabolism and channel the substrate towards production of flavonols or anthocynanins. Decrease in expression of CfCYP706C and increase in accumulation of genkwanin suggested that mannitol treatment may possibly lead to accumulation of genkwanin via suppression of a competitive branch of flavonoids in C. forskohlii.